The Impact of Person Job Fit on Job Satisfaction and its Subsequent Impact on Employees Performance - Iqbal, Muhammad Tahir; Latif, Waqas; Naseer, Wahab (Mediterranean Journal of Social Sciences, 2012)
Humans Resource is considered to be a vital source of growth for the companies, for best utilization of humanresource it is indispensible to align the knowledge, skills and abilities possessed by the employees with the assigned roles in theorganization. The present study reveals the relationship between person job fit, job satisfaction and job performance. This studystudied and analyzed the responses of 251 respondents from various universities in twin cities i.e. Islamabad and Rawalpindi.Results indicated that there exists relationship between person job fit and job satisfaction and job performance and the result ispositive. While the relationship between job satisfaction and job performance is also positive.